Sensory dysfunction associated with repetitive strain injuries of tendinitis and focal hand dystonia: a comparative study. - Byl N; Wilson F; Merzenich M; Melnick M; Scott P; Oakes A; McKenzie A (Journal of Orthopaedic & Sports Physical Therapy, 1996)
Repetitive strain injuries are reaching epidemic levels among workers who perform heavy schedules of rapid alternating movements (eg., computer programmers, data entry workers) or repetitive, sustained, coordinated movements (eg., editors, writers, salespeople). The purpose of this study was to determine if patients with repetitive strain injury demonstrated degraded sensory motor performance with their hands. Sixty age-matched adults were recruited, with 15 each assigned to a healthy adult control group, a healthy musician control group, a tendinitis group, or a focal dystonia group. Four sensory motor subtests from the Sensory Integration and Praxis Test were given to the subjects according to a standardized protocol. Using multiple one-factor analyses of variance in the parametric or nonparametric mode followed by post hoc pairwise testing, no significant differences were found between the healthy controls and the musician controls. On the test of kinesthesia, using the left hand, subjects with tendinitis performed significantly worse than controls and subjects with focal dystonia. Compared with controls, subjects with focal dystonia did significantly worse on graphesthesia and manual form perception (part 1 and part 2). Subjects with focal dystonia also did significantly worse than subjects with tendinitis when using the left hand on graphesthesia and manual form perception (part 2). When treating patients with repetitive strain injury, discriminative sensory motor skills must be carefully assessed and may need to be addressed as part of an effective treatment program.